A new bent-toed gecko (Cyrtodactylus Gray: Squamata: Gekkonidae) from the state of Mizoram, India - Lalremsanga, Hmar Tlawmte; Chinliansiama, Hauzel; Bohra, Sanath Chandra; Biakzuala, Lal; Vabeiryureilai, Mathipi; Muansanga, Lal; Malsawmdawngliana, Fanai; Hmar, Gospel Zothanmawia; Decemson, H.t.; Siammawii, Vanlal; Das, Madhurima; Purkayastha, Jayaditya (Zootaxa, 2022)
Herein we describe a new species of Cyrtodactylus from Lunglei District in the state of Mizoram, India. Based on morphology and ND2 gene sequences, the species was found to be a member of the Cyrtodactylus khasiensis group. The species can be identified by its moderate size (adult SVL 64.9–75.1 mm) with rounded, bluntly conical and feebly keeled dorsal tubercles in 24–28 longitudinal rows; 32–40 paravertebral tubercles between the level of the axilla and the level of the groin; 37–43 mid-ventral scale rows; 3–5 precloacal pores in males and 5–7 pitted precloacal scales in females; 16–18 subdigital lamellae under IV toe; no single row of transversely enlarged subcaudal scales; dorsal markings are dark brown, irregular and distinct; tail with alternating dark and light bands.